Herbicide effects on the establishment of a native bunchgrass in annual grass invaded areas: Indaziflam versus imazapic. Issue 1 (12th March 2021) - Terry, Tyson J.; Madsen, Matthew D.; Gill, Richard A.; Anderson, Val Jo; St. Clair, Samuel B.
Abstract: 1. Annual grass invasion is transforming the western United States and driving a need for restoration techniques that can both reduce exotic annual grass abundance and allow revegetation of native species. Pre‐emergent herbicides can provide control of annual grasses, but when applied concurrently with direct seeding efforts, the herbicide can also impact seeded species. Indaziflam is a relatively new herbicide that may provide extended control of exotic annual grasses, but little is known about its effects when applied at the time of seeding. 2. In this study, we compared indaziflam to imazapic, a popular herbicide used in restoration efforts, to understand how indaziflam affects plant establishment of a native species, bluebunch wheatgrass Pseudoroegneria spicata (Pursh) Á. Löve. We created furrows on half our treatments to limit herbicide concentrations and potentially create a safe‐site for seeding bluebunch wheatgrass. 3. During the 2‐year study, indaziflam provided consistent control of the annual weed, downy brome Bromus tectorum L., whereas imazapic control decreased sharply with time. Indaziflam and imazapic decreased bluebunch wheatgrass seedling emergence by 96% and 46%, and 2 ‐year plant density by 91% and 65%, respectively, compared to non‐herbicide treatments. Both herbicides reduced aboveground biomass of bluebunch wheatgrass by over 85% 2 years after seeding/herbicide application. 4. Furrow treatments mitigated imazapic's effect on bluebunch wheatgrass, but did not limit the impacts by indaziflam. 5. Herbicide can be used in conjunction with direct seeding efforts, but mitigation of the effects to native seeds will depend on herbicide specifics such as mode of action and soil mobility. Abstract : The new herbicide indaziflam has shown stronger downy brome control than imazapic, but it's effects on seeded species are less understood. Here we compare indaziflam against a common herbicide, imazapic, to find that indazaflam is more lethal to native seeds when used in conjunction with restoration seeding efforts.